Permanente Optimierung dynamischer Probleme der Fertigungssteuerung unter Einbeziehung von Benutzerinteraktionen - Dimitrov, Todor (Karlsruher Schriften zur Anthropomatik / Lehrstuhl für Interaktive Echtzeitsysteme, Karlsruher Institut für Technologie ; Fraunhofer-Inst. für Optronik, Systemtechnik und Bildauswertung IOSB Karlsruhe, 2015)
Despite huge research efforts only simple scheduling algorithms assist humans in their daily work. This work presents a comprehensive concept for a permanent running algorithmic scheduler intelligently collaborating with the humans. The developed approaches provide prompt reactions on manufacturing events and intelligent rescheduling based on analysis of the optimization potential and demand. The practicability of the presented approaches is proved by dynamic simulations with real data.